Selective Parathyroid Autotransplantation During Total Thyroidectomy for Papillary Thyroid Carcinoma: A Cohort Study - Qiu, Yuxuan; Xing, Zhichao; Qian, Yuanfan; Fei, Yuan; Luo, Yan; Su, Anping (Frontiers in Surgery, 2021)
Purpose The relationship between the selective parathyroid gland (PG) autotransplantation and hypoparathyroidism is still not completely clear. The aim was to ascertain whether the number of autotransplanted PGs affected the incidence of hypoparathyroidism and recovery of parathyroid function in the long-term for patients with papillary thyroid carcinoma (PTC). Methods A retrospective cohort study included all patients with PTC who had underwent primary total thyroidectomy with central neck dissection between January 2013 and December 2017. The patients were divided into 3 groups (0, 1, and 2 PGs autotransplanted, respectively). Results Of the 2,477 patients, 634 (25.6%) received no PG autotransplantation, 1078 (43.5%) and 765 (30.9%) were autotransplanted 1 and 2 PGs, respectively, and the incidence of permanent hypoparathyroidism (>1 year) was 1.7%, 0.7%, and 0.4% (P = 0.0228). Both 1 or 2 PGs autotransplanted increased the incidence of transient biochemical hypoparathyroidism (odds ratio [OR], 1.567; 95% confidence interval [CI], 1.258 – 1.953; P < 0.0001; OR, 2.983; 95% CI, 2.336 – 3.810; P < 0.0001, respectively) but reduced the incidence of permanent hypoparathyroidism (OR, 0.373; 95% CI, 0.145 – 0.958; P = 0.0404; OR, 0.144; 95% CI, 0.037 – 0.560; P = 0.0052, respectively). Both 1 or 2 PGs autotransplanted did not independently influence the occurrence of hypocalcemia symptoms. Conclusion Selective parathyroid autotransplantation is less likely to lead to postoperative symptomatic hypocalcemia, although it could lead to a transient decrease in parathyroid hormone. However, in the long run, it is still an effective strategy to preserve parathyroid function.